Modelling the Dynamics of Language Change: Logistic Regression, Piotrowski's Law, and a Handful of Examples in Polish. Issue 1 (2nd January 2023) - Górski, Rafał L.; Eder, Maciej
ABSTRACT: The study discusses modelling diachronic processes by logistic regression. The phenomenon of nonlinear changes in language was first observed by Raimund Piotrowski (hence labelled as Piotrowski's law), even if actual linguistic evidence often speaks against using the notion of a 'law' in this context. In our study, we apply logistic regression models to changes which occurred between 15 th and 18 th century in the Polish language. The attested course of the majority of these changes closely follow the expected values, which proves that the language change might indeed resemble a nonlinear phase change scenario. We also extend the original Piotrowski's approach by proposing polynomial logistic regression for these cases which can hardly be described by its standard version. Also, we propose to consider individual language change cases jointly, in order to inspect their possible collinearity or, more likely, their different dynamics in the function of time. Last but not least, we evaluate our results by testing the influence of the subcorpus size on the model's goodness-of-fit.